The impact of river landform changes caused by geohazards on the economic development of ecotourism in Sabah, Malaysia - Zulayti Zakaria; Ang Kean Hua (ResearchGate, 2024)
The impact of river landform changes caused by geohazards on the economic development of ecotourism in Sabah, Malaysia is a highly significant and crucial topic that necessitates extensive analysis, comprehension, and thorough understanding in order to comprehend the multifaceted consequences and ramifications. It is imperative to explore and scrutinize the intricate interplay between the alterations in river landforms induced by geohazards, such as natural disasters and environmental upheavals, and their profound influence on the economic growth and prosperity of the burgeoning ecotourism sector in Sabah, Malaysia. This comprehensive investigation holds immense value in unraveling the intricate dynamics and intricacies inherent in this intricate and complex relationship. By delving deep into the intricate mechanisms and multifarious aspects that underlie the interdependence of geohazards-induced river landform transformations and the economic development of ecotourism in Sabah, Malaysia, researchers and stakeholders alike can gain invaluable insights that can pave the way towards well-informed decision-making, sustainable growth, and effective management strategies. Consequently, the expansion of knowledge and understanding in this pivotal domain can potentially lead to the formulation and implementation of robust measures, policies, and initiatives that can mitigate the adverse effects of geohazards on river landforms, foster the resilience and adaptability of the ecotourism industry, and ultimately cultivate a harmonious balance between economic progress and environmental conservation in Sabah, Malaysia.